Intratumoral expression of FoxP3-positive regulatory T-cells in T-cell lymphoma: no correlation with survival - Lundberg, Josefine (Ups J Med Sci, 2019)
Background. In cancer, regulatory T-cells (Tregs) were previously believed to inhibit tumor immunity, leading to reduced survival. However, in hematologic malignancies, including T-cell lymphoma (TCL), a correlation between increased numbers of tumor-infiltrating Tregs and a favorable prognosis has been reported. We aimed to investigate the expression of the Treg biomarker forkhead box protein 3 (FoxP3) in TCL in immunocompetent individuals and explore a possible correlation to overall survival. Methods. In total, 35 diagnostic biopsies of TCL were stained using a FoxP3-specific monoclonal antibody (clone 236A/E7). Visual scoring was performed by counting positive cells in 15 high-power fields. Clinical data were collected retrospectively from medical records. Results. All the TCLs contained FoxP3(+) cells, median 342 FoxP3(+) cells/mm(2) (range 1–3047). The degree of intratumoral expression of FoxP3 varied between the different subtypes of TCL, with the highest frequency found in angioimmunoblastic TCL. The frequency of intratumoral FoxP3(+) cells had no impact on overall survival; neither when using a cutoff value of 200 FoxP3(+) cells/mm(2) (P = 0.84) nor with FoxP3 as a continuous variable (P = 0.63). Conclusions. Intratumoral Tregs are frequently found in TCL in immunocompetent individuals. In this heterogeneous group of TCL, there was no correlation between the density of intratumoral FoxP3(+) cells and overall survival.